Rites of Treatment in Eastern Africa and Rite Vocabulary According to Literary Sources - Fattakhova, Aida R.; Melnikova, Maria D.; Gromova, Nelli V. (Journal of History Culture and Art Research, 2017)
Rites as the reflection of religious ideas and everyday traditions are of great importance to understand the national picture of the world among the representatives of different peoples. The article examines the rites of the East African society aimed at healing; the ritual vocabulary, saturated with national and cultural information is analyzed and the translation decisions in the transfer of cultural-labeled units reflecting the realities of the Swahili culture carriers are demonstrated. Taking into account the nature of the presented material, the methods widely used in historical and ethnographic and philological research were used during the present study: descriptive, systemic, and semantic one. Nowadays, traditional medicine and conventional medicine go hand in hand in Eastern Africa countries, particularly in Tanzania, complementing each other in the treatment and the prevention of diseases, the preservation and the strengthening of human health. In the case when modern medicine is powerless, doctors recommend that patients turn to herbalists. At the same time, it is impossible to confuse healers who use grasses and other natural resources in their work, passing their experience from generation to generation, with sorcerers and the sorcerers not engaged in treatment. The conclusions formulated in the process of research are of practical importance and can be used by the experts of ethnography, ethnology, translation studies, linguistics, cultural studies and historical science, as well as during the lectures on the study of lexicology in Swahili.